Cloning and characterization of the 5′-flanking region of the canine growth hormone gene - Lantinga-van Leeuwen, Irma S; Timmermans-Sprang, Elpetra A.P; Mol, Jan A (Molecular and cellular endocrinology, 2002)
The growth hormone (GH) gene is expressed in a variety of tissues outside the pituitary, including the mammary gland. GH expression in the mammary gland is stimulated by progestins. The local synthesis of mammary GH may provide a highly proliferative environment within the mammary gland that may contribute to the development or progression of mammary tumours. To elucidate the mechanism regulating mammary GH expression, we cloned the 5′-flanking region of the canine GH gene using inverse polymerase chain reaction. Gel-shift experiments showed that several sequences in the 5′-flanking region of the GH gene bind mammary nuclear proteins and may be involved in basal and progesterone-induced mammary GH expression. Sequence analysis and comparison with the GH promoters of human, rat, and mouse genes revealed a number of shared binding sites for transcription factors such as Pit-1, which is involved in pituitary GH expression, and for factors involved in the differentiation of lymphoid cells. Moreover, a putative binding site for the progesterone receptor (PR) was identified in all promoters, indicating that the progestin-induced expression of GH in mammary tissue is most probably a direct effect of activated PRs on the GH gene promoter and that this may occur in various species.